Pendidikan Dalam Meningkankan Sumber Daya Manusia Di Sma Siger Bandar Lampung - Dian Puspita; Miswan Gumanti; Rara Marselina Jupon; Sariyah Astuti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
For communities to effectively manage and preserve the environment and resources, education is crucial. The goal of classroom learning is to influence students' attitudes and actions. The majority of educational institutions in Lampung Province experiencing teacher shortages are SMA Siger. The first private institution in Bandar Lampung, located in Bandar Lampung City, faces various challenges, including poor teaching effectiveness, additional instructors who must meet specific professional demands, and teachers who must be forward-thinking, enthusiastic about development and renewal, always up-to-date with innovations, and enthusiastic about academic achievement. To identify alternative strategies and methods used in managing human resources in educational organizations, this study applies a library research method, which includes collecting and analyzing data. The following will encourage the development of teacher competency. Furthermore, it is hoped that educators' perspectives and beliefs will continue to develop an ideology (understanding) regarding the importance of competency.